If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 8a = 50 + 6a + -9a Combine like terms: 6a + -9a = -3a 6 + 8a = 50 + -3a Solving 6 + 8a = 50 + -3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3a' to each side of the equation. 6 + 8a + 3a = 50 + -3a + 3a Combine like terms: 8a + 3a = 11a 6 + 11a = 50 + -3a + 3a Combine like terms: -3a + 3a = 0 6 + 11a = 50 + 0 6 + 11a = 50 Add '-6' to each side of the equation. 6 + -6 + 11a = 50 + -6 Combine like terms: 6 + -6 = 0 0 + 11a = 50 + -6 11a = 50 + -6 Combine like terms: 50 + -6 = 44 11a = 44 Divide each side by '11'. a = 4 Simplifying a = 4
| 12-5u=43 | | p=2l+10 | | x+3x+4x=24 | | 2m+3m-17m=80-m | | 3-3/8X=1/4X | | 1/4(28x-8) | | x+8a=50+ax-9a | | 26/39 | | 1/4X+1/5X=9 | | -3(x+2)=16-2 | | 5-2(x-5)=4x-6 | | 2(2t-5)=20-t | | -28+15-27z=31 | | 1/8y^-5 | | x+8a=50ax-9a | | 5/6X=3-11/12X | | p=x+1+4+4+2+2+x+2+1 | | 6x-3=5x-10x+8 | | 0.7(x+200)=0.75x-225 | | 3(a-2)=6a-(3a+6) | | .2-2=8 | | 3x^2+17x+4=0 | | 5x=5x-3+x-9 | | X/7-X/14+9=X+9 | | 8x+39=2x+15 | | (2/x-3)=(-5/x+5)+(9/(x-3)(x+5)) | | 3x+2x+8=10x-7 | | 14.2=-6.8 | | -4x-2x-10=2x-34 | | 120-(-27)= | | 1/3x-15=10 | | 5-7[6-(4y-6)]= |